Ethical World: A Study on the Ethical Thought in the East and West - Nayak, G C (Journal of Dharma, 1996)
Thomas Kadankavil, Ethical World: A Study on the Ethical Thought in the East and West. Bangalore: Dharmaram Publications, 1995, pp. wi + 345